THE CORRELATION BETWEEN STUDENTS’ SPEAKING AND WRITING ABILITY AMONG HIGH SCHOOL STUDENTS - Riska Elvita; Nunun Indrasari (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
The objective of this research was to know whether there was a correlation between students’ speakingand writing ability of descriptive text at the second semester of tenth grade of SMAN 1 Lemong PesisirBarat in 2015/2016 academic year.The research methodology of this research was correlation research, since the researcher wanted to know the correlation between students’ speaking and writing ability of descriptive text. The population of the research was taken from the students at the second semester of tenth grade of SMAN 1 Lemong Pesisir Barat which consisted of 130 students. In taking the sample of the research, the researcher used cluster random sampling technique. The sample was X2 class which consisted of 32 students. In collecting the data, the researcher used instrument in the form of oral test about describing an object for speaking test and essay testabout descriptive text for writing test. After giving try out, the researcher gave the test and then analyzed the data by using Pearson’s Product Moment formula.The result of the hypothetical test was 0.8, and then it was consulted to rcritical. The result of rcritical with significant level 0.05 was 0.361. Due to robserved is higher than rcritical (0.8 > 0.361), the conclusion of the research is that there is a correlation between students’ speaking and writing ability of descriptive text at thesecond semester of tenth grade of SMAN 1 Lemong Pesisir Barat in 2015/206 academic year.DOWNLOAD ABSTRACT